Elaboration of technological card as a tool for increasing quality of quasiprofessional activity of the future teachers of informatics - Шовкун, Віталій Віталійович (ScienceRise: Pedagogical Education, 2016)
The speed of informatization of society and the spreading of means of information-communication technologies (ICT) condition the new approaches to organization of the learning process, especially in general educational institutions. Informatization of education favors the rise of effectiveness and flexibility of education, makes it modern and adapts it to the international standards. The modern educational technologies must be reflected, in the first turn, in the content component of disciplines, connected with methodology of teaching informatics, organization of practice at school, because different educational institutions have the different level of technical equipment. All this pushed us to the creation of technological card for student-practician, the future teacher of informatics. Using it in their quasiprofessional activity, students can systematize information, received at the first stages of practice, and analyze the state of technical and informational environment of educational institution. The training of competent teacher of informatics, able to play the role of innovator, who can create the situation of expedient use of certain technology in the learning-upbringing process, favor the pupils’ preparation for the life in informational world according to the requirement of modern society, is a socially-important problem